Small mammal assemblages in land-reclaimed areas: do historical soil use changes and recent anthropisation affect their dominance structure?. Issue 3 (3rd May 2020) - Battisti, Corrado; Dodaro, Giuseppe; Di Bagno, Ermellina; Amori, Giovanni
Abstract : We report a case of structural oversimplification in a small mammal assemblage, indirectly obtained by owl pellets (central Italy), where mice (Rodentia Muridae) largely dominated both in abundance and biomass (about 95%). We hypothesise that this fact could be due to: (i) recent anthropisation, which induced both an expected increase of synanthropic generalist species (mice, Muridae) and a sharp reduction in high trophic level species (shrews, Soricomorpha), and, (ii) historical land reclamation occurred in the 19th century, which changed the edaphic characteristics, and consequently inducing an unexpected local absence of common digging species (yet reported by literature for the Maremma plain) everywhere diffused along Italian peninsula: the ubiquitous Microtus savii (Microtidae), and the moles ( Talpa spp., Talpidae). These two causal processes, acting at different temporal scales, could strongly affect the structure of the small mammal assemblage, dominated by a single taxonomic guild (Muridae), therefore similar to neighbouring insular assemblages (Tuscan Archipelago).